Markers of T cell activation and exhaustion in plasma are associated with persistent symptoms up to 18 months following mild SARS-CoV-2 infection - Ueland, Thor; Cox, Rebecca Jane; Michelsen, Annika E.; Fjelltveit, Elisabeth Berg; Otterdal, Kari; Dahl, Tuva; Zhou, Fan; Elyanow, Rebecca; Aukrust, Pål; Blomberg, Bjørn; Halvorsen, Bente E.; Langeland, Nina (Frontiers in Immunology, 2025)
BackgroundPersistent symptoms following SARS-CoV-2 is an increasing problem after COVID-19 disease. The pathogenesis of this persistent post Covid-19 Condition (PCC) is, however, largely unknown. We hypothesized that persistent T cell activation and exhaustion play a role in PCC development.MethodsWe examined plasma levels of soluble (s) CD25, TIM-3 and LAG-3, all markers of T cell activation/exhaustion, by enzyme immunoassays in 170 home-isolated and 53 hospitalized patients for up to 18 months after COVID-19 in relation to persistent symptomatology.ResultsOur major findings were: (i) Cases with persistent dyspnea and fatigue had markedly higher sCD25 at 6–18 months with a more modest increase in sTIM-3. (ii) Cases with memory problems at 12–18 months had increased sLAG-3 iii) sCD25 correlated with SARS-CoV-2 antibody titers and microneutralization titers only in cases with PCC while sTIM-3 correlated with these parameters irrespectively of symptoms. iv) Although hospitalized patients had markedly elevated levels of T cell activation/exhausting markers during follow-up, there was no relation to PCC symptoms.ConclusionOur study indicates a role for T cell activation/exhaustion in PCC following home isolated COVID-19 infection, with somewhat different patterns of sCD25, sTIM-3 and sLAG-3, but not in hospitalized COVID-19 patients where disease severity may be more important.